Long-term treatment with human immunoglobulin for antisynthetase syndrome-associated interstitial lung disease. (July 2019) - Huapaya, J.A.; Hallowell, R.; Silhan, L.; Pinal-Fernandez, I.; Casal-Dominguez, M.; Johnson, C.; Albayda, J.; Paik, J.J.; Lin, C.T.; Hussien, A.; Mammen, A.L.; Christopher-Stine, L.; et al.
Abstract: Background: Interstitial lung disease-associated antisynthetase syndrome (AS-ILD) carries significant morbidity and mortality. Corticosteroids and immunosuppressive drugs are the mainstay of treatment. Human immunoglobulin (IVIg), an immunomodulator without immunosuppressive properties, is effective in myositis but the evidence supporting its use in ILD is scarce. Objective: To describe clinical outcomes of AS-ILD patients receiving IVIg. Methods: Retrospective analysis of AS-ILD patients. Linear mixed models using restricted maximum likelihood estimation was used to estimate the change in lung function and corticosteroid dose over time. Results: Data from 17 patients was analyzed. Median follow-up was 24.6 months. Fourteen patients had refractory disease. The mean percent-predicted forced vital capacity (FVC%) (p = 0.048) and percent-predicted diffusing capacity of the lung for carbon monoxide (DLCO%) (p = 0.0223) increased over time, while the mean prednisone dose (p < 0.001) decreased over time. Seven patients achieved a >10% increase in FVC%, including two who used IVIg as initial treatment. Five patients showed a >10% increase in DLCO% and TLC%. Nine (53%) patients experienced side effects. Conclusions: IVIg may be a useful complementary therapy in active progressive AS-ILD but is associated with potential side effects. Fssssurther investigation is required to determine the value of IVIg as an initial treatment in AS-ILD. Highlights: IVIg stabilized the lung function of patients with interstitial lung disease. IVIg increased the mean FVC% and DLCO% over time in patients with antisynthetase syndrome. IVIg decreased the mean prednisone dose over time in patients with antisynthetase syndrome.